Simulation Study of Stand-Alone Photovoltaic System Design with Battery and Supercapacitorr - Norashid, Nur Sharina Farisha; Hamdan , Rohaiza (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays PV system has been used in many countries around the world. A PV system is composed of one or more solar panels combined with an inverter and other electrical and mechanical hardware that use energy from the sun to generate electricity. There are many types of photovoltaic solar system designs and can be listed into three types, on-grid, off-grid, and hybrid-grid. In this project, an off-grid photovoltaic solar system design is chosen. However, since solar photovoltaic systems are fully dependent on the weather and temperature, this might interrupt the continuous supply of electricity to the household.  To alleviate the uncertainty of photovoltaic systems the home appliance, this study will implement hybrid energy storage by utilizing the application of a battery and supercapacitor. Hybrid energy storage will improve the efficiency of grid-connected photovoltaic systems. They are used to improve the quality of output power from the photovoltaic system. The variation of output power depends heavily on weather conditions, leading to adversely affecting the power system’s stability. Battery and supercapacitor are the best work together since the battery has high energy density while the supercapacitor has high power density. The supercapacitor is introduced in this paper to extend battery performance, and lifetime and reduce maintenance costs. The results are tested and analyzed for a battery system with supercapacitors integrated.